An introduction to polymer chemistry - Margerison, D.; East, G. C. (Commonwealth and international library. Intermediate chemistry division., 1967)
An Introduction to Polymer Chemistry focuses on the fundamental chemistry of synthetic organic polymers of high molecular weight. This book explains the basic principles of polymer chemistry, from significant methods of molecular weight determination to the simpler mechanisms of polymerization. The osmotic, light scattering, and viscosity methods of molecular weight determination are fully discussed together with the kinetics of selected examples of condensation and free-radical addition polymerization. The main features of ionic polymerization are also elaborated. This text, however, does not.